The Long-term Outcome of Sleeve Gastrectomy in Managing Obstructive Sleep Apnea in Prader–Willi Syndrome Patients: A Case Series - Safa Eltahir; Mohammed Alzaid; Gawahir Mukhtar; Wadha Alotaibi (Dr. Sulaiman Al Habib Medical Journal, 2020)
Background: Prader–Willi syndrome (PWS) is a genetic disorder with multisystem involvement. Bariatric laparoscopic Sleeve Gastrectomy (SG) surgery has been proposed as a means of weight control in PWS patients. There is some controversy around sleeve gastrectomy as a management strategy in PWS to control Obstructive Sleep Apnea (OSA). Case-Series: In this case series we are questioning the effectiveness of bariatric gastric sleeve surgery as a long-term solution for weight control. Therefore, we followed up four patients with PWS in our center who had SG and evaluated their growth parameters along with symptoms of sleep disordered breathing. The median age of patients in this group was 7.5 years. There were three males and one female. The average Body Mass Index (BMI) prior to SG was 40.5. The average BMI after SG, at 5–7 years, was 40.8. This shows an insignificant effect of SG on BMI and control of OSA on follow-up over more than 5 years. Conclusion: We believe that SG has limited and transient success for obesity management in PWS patients, especially in the absence of a multidisciplinary team that can provide behavioral therapy, nutritional plan, and psychosocial support. Further studies are necessary to compare the long-term outcome sleeve gastrectomy with behavioral and strict nutritional therapy.